Constraints on the frontal crustal structure of a continental collision from an integrated geophysical research: The central‐western Betic Cordillera (SW Spain) - A. Ruiz‐Constán; A. Pedrera; J. Galindo‐Zaldívar; J. Pous; J. Arzate; F. J. Roldán‐García; C. Marin‐Lechado; F. Anahnah (Geochemistry, Geophysics, Geosystems, 2012)
Mélange rocks outcrop widely in the central and western frontal sectors of the Betic Cordillera, as in many other collisional orogens where they form part of the accretionary wedges. Extrusion of Triassic plastic clays and evaporites was favored by the progressive accretion of the Betic External Zones, mixing rocks of different provenance and forming a synorogenic frontal mélange unit. MT data coupled with gravity data are a valid combined methodology to characterize the geometry of these mélange units, since the characterization of plastic rocks geometry is usually uncertain using seismic techniques. The results correlate well with known geological features (sedimentary basins, calcareous ranges, evaporitic rocks) and reveal the deep geometry. A resistive body, slightly dipping toward the SE, points to the continuity of the Iberian Massif below the Guadalquivir basin (2°) and the External Zones (6–8°). To the south, gravity models show the Iberian continental crust subducting below the Internal Zones with a roughly 20–35° slope. The main conductive bodies are related to the location of evaporitic rocks involved in the frontal mélange. They overlie the Iberian Massif and, southwards, the frontal Jurassic and Cretaceous limestone sequences of the External and Median Subbetics. In this setting, thick plastic rock units placed above the foreland could act as a lubricant facilitating continental subduction, and being progressively accreted toward a frontal mélange.